2008
DOI: 10.1002/cphc.200700625
|View full text |Cite
|
Sign up to set email alerts
|

Sol‐Gel‐Sol Transition of Gold Nanoparticle‐Based Supramolecular Hydrogels Induced by Cyclodextrin Inclusion

Abstract: Hydrogel systems are attractive for different biomedical applications because of their favorable biocompatibility, such as controlled drug delivery and tissue engineering.[1] A number of examples of temperature-, light-, and pH-responsive hydrogel systems have been reported. [2] On the other hand, gold nanoparticles (GNPs) have also attracted much scientific and technological attention due to their excellent physical and chemical characteristics. For example, they are used for tracing cellular biological samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
0
32
0
3
Order By: Relevance
“…Mono‐6‐deoxy‐6‐( p ‐tolylsulfonyl)‐β‐CD (6‐OTs‐β‐CD) and SH‐β‐CD were synthesized as described in Ref. , and 1 H NMR verified the synthesis of β‐CD derivates (Figure S1, Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…Mono‐6‐deoxy‐6‐( p ‐tolylsulfonyl)‐β‐CD (6‐OTs‐β‐CD) and SH‐β‐CD were synthesized as described in Ref. , and 1 H NMR verified the synthesis of β‐CD derivates (Figure S1, Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…The appearance of the isosbestic point in the absorption spectra of the interaction of (mono-6-thio--CD)-CdTe QDs with neutral red indicated that HNR + didn't form aggregates on the surface of (mono-6-thio--CD)-CdTe QDs. NR formed the inclusion complex with S--CD on the surface of (mono-6-thio--CD)-CdTe QDs [23] which made the equilibrium between HNR + and NR shift towards NR. On the surface of (mono-6-thio--CD)-CdTe QDs appeared charge neutralization occurred due to the combination of HNR + with SCH 2 COO on the surface of (mono-6-thio--CD)-CdTe QDs.…”
Section: Absorption Spectramentioning
confidence: 99%
“…The synthesis of mono-6-thio--CD [23] -Cyclodextrin (70.0 g, 62 mmol) was suspended in water (550 mL), and NaOH (6.6 g, 165 mmol) in water (20 mL) was added dropwise over 6 min. The suspension became homogeneous and slightly yellow before the addition was complete.…”
Section: 21mentioning
confidence: 99%
“…Chen et al. reported the preparation of gold‐nanoparticle‐based supramolecular hydrogels induced by cyclodextrin inclusion 36. The thio‐β‐CDs, covalently adsorbed on Au nanoparticles, formed inclusion complexes with the propylene oxide (PPO) blocks of Pluronic F127, giving rise to a network structure.…”
Section: Nanoparticle Assembly Directed By Supramolecular Macrocyclesmentioning
confidence: 99%